Sigma-1 Receptor Plays a Negative Modulation on N-type Calcium Channel - Zhang, Kang; Zhao, Zhe; Lan, Liting; Wei, Xiaoli; Wang, Liyun; Liu, Xiaoyan; Yan, Haitao; Zheng, Jianquan (Frontiers in Pharmacology, 2017)
The sigma-1 receptor is a 223 amino acids molecular chaperone with a single transmembrane domain. It is resident to eukaryotic mitochondrial-associated endoplasmic reticulum and plasma membranes. By chaperone-mediated interactions with ion channels, G-protein coupled receptors and cell-signaling molecules, the sigma-1 receptor performs broad physiological and pharmacological functions. Despite sigma-1 receptors have been confirmed to regulate various types of ion channels, the relationship between the sigma-1 receptor and N-type Ca2+ channel is still unclear. Considering both sigma-1 receptors and N-type Ca2+ channels are involved in intracellular calcium homeostasis and neurotransmission, we undertake studies to explore the possible interaction between these two proteins. In the experiment, we confirmed the expression of the sigma-1 receptors and the N-type calcium channels in the cholinergic interneurons (ChIs) in rat striatum by using single-cell reverse transcription-polymerase chain reaction (scRT-PCR) and immunofluorescence staining. N-type Ca2+ currents recorded from ChIs in the brain slice of rat striatum was depressed when sigma-1 receptor agonists (SKF-10047 and Pre-084) were administrated. The inhibition was completely abolished by sigma-1 receptor antagonist (BD-1063). Co-expression of the sigma-1 receptors and the N-type calcium channels in Xenopus oocytes presented a decrease of N-type Ca2+ current amplitude with an increase of sigma-1 receptor expression. SKF-10047 could further depress N-type Ca2+ currents recorded from oocytes. The fluorescence resonance energy transfer (FRET) assays and co-immunoprecipitation (Co-IP) demonstrated that sigma-1 receptors and N-type Ca2+ channels formed a protein complex when they were co-expressed in HEK-293T cells. Our results revealed that the sigma-1 receptors played a negative modulation on N-type Ca2+ channels. The mechanism for the inhibition of sigma-1 receptors on N-type Ca2+ channels probably involved a chaperone-mediated direct interaction and agonist-induced conformational changes in the receptor-channel complexes on the cell surface.